Neurological manifestations and complications of COVID-19: A literature review - Ahmad, Imran; Rathore, Farooq Azam (Journal of clinical neuroscience, 2020)
•COVID-19 primarily affects the lungs and respiratory system.•Some patients may present with neurological symptoms.•Most common CNS manifestations include headache, dizziness and encephalopathy.•Most frequently reported PNS manifestations include loss of smell and taste which may be a presenting symptom as well.•Neurological complications are more common in severely ill COVID-19 patients. The Coronavirus disease due to SARS-CoV-2 emerged in Wuhan city, China in December 2019 and rapidly spread to more than 200 countries as a global health pandemic. There are more than 3.5 million confirmed cases and around 165,000 to 243,000 fatalities. The primary manifestation is respiratory and cardiac but neurological features are also being reported in the literature as case reports and case series. The most common reported symptoms to include headache and dizziness followed by encephalopathy and delirium. Among the complications noted are Cerebrovascular accident, Guillian barre syndrome, acute transverse myelitis, and acute encephalitis. The most common peripheral manifestation was hyposmia. It is further noted that sometimes the neurological manifestations can precede the typical features like fever and cough and later on typical manifestations develop in these patients. Hence a high index of suspicion is required for timely diagnosis and isolation of cases to prevent the spread in neurology wards. We present a narrative review of the neurological manifestations and complications of COVID-19. Our aim is to update the neurologists and physicians working with suspected cases of COVID-19 about the possible neurological presentations and the probable neurological complications resulting from this novel virus infection.